Rigid-only versus combined rigid and flexible percutaneous nephrolithotomy: a systematic review - Cracco, Cecilia M.; Knoll, Thomas (Minerva urologica e nefrologica, 2017)
Introduction: Percutaneous nephrolithotomy (PNL) is usually performed worldwide with a rigid-only antegrade approach. Daily practice suggests that adding flexible nephroscopy and/or ureteroscopy to conventional rigid PNL might improve its efficacy and safety, but available evidence is weak. Appraisal of reliable outcomes of such PNL techniques would better guide intraoperative choices and optimize surgical results. Therefore, our objective was to systematically review relevant literature comparing the outcomes of rigid-only PNL and combined flexible PNLs (adding flexible nephroscopy and/or flexible ureteroscopy) for the treatment of large and/or complex upper urinary tract calculi, with regard to efficacy and safety. Evidence acquisition: Ovid MedLine, PubMed, Scopus and Web of Science databases were searched in August 2016 to identify relevant studies. Article selection was performed according to the Preferred Reporting Items for Systematic Review and Meta-analysis criteria. Evidence synthesis: Six articles reporting on 666 patients were included: two randomized controlled trials, two retrospective comparative studies and two case series ≥50 patients (one prospective and one retrospective). A narrative synthesis of minor evidences was also prepared. The adjunct of flexible nephroscopy and/or ureteroscopy provided better stone-free rates (range 86.7-96.97%), through a single percutaneous access most of the times and in any position, reducing the need for second-look procedures. Safety of the combined flexible procedures was improved to a variable degree, with a consensual reduction of the mean hospital stay (range 5.1-7 days). Conclusions: The current evidence suggests that patients with large and/or complex urolithiasis might benefit from the adjunct of flexible nephroscopy and/or ureteroscopy to rigid PNL.